Le tourisme scientifique dans les Alpes françaises : un laboratoire pour la médiation scientifique et la recherche - Yannick Vialette (Institut de Géographie Alpine, 2021)
This contribution focuses on scientific mediation implemented within scientific tourism initiatives in mountain areas. Three case studies in the French Alps support this research: the Jardin Alpin du Lautaret of the University of Grenoble Alpes, the CREA Mont-Blanc, a private research center organizing participatory science and student travel abroad programs and the scientific hut to hut trekking routes in the Ecrins National Park, organized jointly with a scientific research project (Labex ITEM, Reflab). Scientific tourism and mediation are first defined. Next, a quantitative and qualitative approach (with interviews and participant observations) allows us to understand the impact and role of scientific mediation within tourism. Results show a high level of interest of the issue within involved publics and a close connection between experience and knowledge. It appears that it is also a tool for public awareness of the challenges of our modern societies.